Nutritional and functional evaluation of 17 quinoa (Chenopodium quinoa Willd) accessions cultivated in the Andean area of Peru - Ponce de León Saavedra, Pámela (2021)
The objective was to evaluate the nutritional composition and functional potential of quinoa accessions from Cuzco and cultivated in Huancayo. Were evaluated 17 accessions of Huancayo, 7 of low saponin content (< 0.11) and 10 of high. The average results of moisture, protein, fat, ash, crude fiber and carbohydrates were 9.79% ± 0.01, 17.27% ± 0.02, 6.76% ± 0.01, 2.10% ± 0.05, 3.07% ± 0.04 y 70.81% ± 0.11 respectively. The in vitro digestibility of starches and protein was 32.23% ± 0.008 and 83.6% ± 0.002 respectively. The total dietary fiber was 7.44% ± 1.86. In Cuzco accessions, the average results of moisture, protein, fat, ash, crude fiber and carbohydrates were 11.29% ± 0.02, 16.46% ± 0.04, 7.67% ± 0.01, 1,97% ± 0.01, 2.52% ± 0.01 and 71.38% ± 0.04 respectively. The in vitro digestibility of starch and proteins was 72.52% ± 0.001 and 83.53% ± 0.007, respectively. The total dietary fiber was 7.02% ± 1.57. Among the quinoa accessions of Huancayo and their corresponding originals from Cuzco, content of protein, crude fiber, carbohydrates, total dietary fiber, total phenolic compounds, and in vitro digestibility of protein did not show significant differences (p ˃ 0.05).